Nutritional Balance of Sugarcane Varieties Under Irrigation Depths and Nitrogen Fertilization - de Mendonça, Marcos Ferreira; Dantas Neto, José; de Oliveira, Emídio Cantídio Almeida; Menegaz Meneghetti, Luana Aparecida; Custódio, Alisson Silva Costa; da Silva, Patrícia Ferreira (Communications in Soil Science and Plant Analysis, 2025)
Nutritional homeostasis is essential if there is to be a balance in the nutritional balance, i.e. the requirement and export of nutrients by plants. This study aimed to evaluate the nutritional balance through the export and requirement of nutrients in sugarcane varieties under different irrigation depths and doses of nitrogen fertilization. The experiment was conducted for two consecutive years. The experimental design was randomized blocks in a subdivided strip scheme with four replications. The treatments consisted of four irrigation depths (L1 = 12, L2 = 45, L3 = 100, and L4 = 125% of crop evapotranspiration (ETc), plant cane), and (L1 = 10, L2 = 40, L3 = 100, and L4 = 125% of ETc, 3w), four doses of nitrogen (N1 = 0, N2 = 50, N3 = 100, and N4 = 200 kg ha −1 of N) and two varieties of sugarcane (RB92579 and RB002754). Homeostasis was positively influenced by the increase in irrigation depth, and the opposite occurred with the nitrogen doses applied. The export and demand for plant cane and ratoon cane are influenced by irrigation depths. Certain cane varieties have varying effects on the requirement for nitrogen, phosphorus, potassium, calcium, magnesium, and sulfur. Increasing nitrogen doses can reduce the export of phosphorus and magnesium.